Ecotoxicological aspects related to the presence of pharmaceuticals in the aquatic environment - Santos, Lúcia (2013)
Pharmaceuticals are biologically active and persistent substances which have been recognized as a continuing threat to environmental stability. Chronic ecotoxicity data as well as information on the current distribution levels in different environmental compartments continue to be sparse and are focused on those therapeutic classes that are more frequently prescribed and consumed. Nevertheless, they indicate the negative impact that these chemical contaminants may have on living organisms, ecosystems and ultimately, public health. This article reviews the different contamination sources as well as fate and both acute and chronic effects on non-target organisms. An extensive review of existing data in the form of tables, encompassing many therapeutic classes is presented.